Enhancing Product Sales through the Implementation of an E-Commerce-Based Marketing System - Putri Prasetyaningrum; putry wahyu setyaningsih; Ozzi Suria; Ibnu Rivansyah Subagyo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This service project is titled "Enhancing Product Sales through the Implementation of an E-Commerce-Based Marketing System." The partner IbM faces several challenges, including (1) the absence of an e-commerce system for marketing products and (2) difficulties for customers in purchasing products. The objectives of this program are (1) to implement an e-commerce system to introduce products and reach a broader market, thereby increasing sales, and (2) to assist customers in making transactions more easily. The service program is conducted in two forms: First, the design of an e-commerce system to improve customer communication that is not limited by geographical factors, allowing direct targeting of the desired market share without intermediaries. Second, the creation of an e-commerce system to boost partner sales and simplify sales transactions. The implementation of this program is designed in four stages: (1) Coordination and preparation phase, (2) Design phase, (3) Application of science and technology phase, and (4) Evaluation and refinement phase.